Women's Participation in Peace Negotiations and the Durability of Peace - Jana Krause; Werner Krause; Piia Bränfors (International Interactions, 2018)
There is an emerging consensus that women's participation in peace negotiations contributes to the quality and durability of peace after civil war. However, to date, this proposition has remained empirically untested. Moreover, how women's participation may contribute to durable peace has not been systematically explored. This article uses a mixed method design to examine this proposition. Our statistical analysis demonstrates a robust correlation between peace agreements signed by female delegates and durable peace. We further find that agreements signed by women show a significantly higher number of peace agreement provisions aimed at political reform, and higher implementation rates for provisions. We argue that linkages between women signatories and women civil society groups explain the observed positive impact of women's direct participation in peace negotiations. Collaboration and knowledge building among diverse women groups contributes to better content of peace agreements and higher implementation rates of agreement provisions. We substantiate this argument with qualitative case study evidence and demonstrate how collaboration between female delegates and women civil society groups positively impacts peace processes. Our findings support the assumption that women's participation in peace negotiations increases the durability and the quality of peace.
Keywords: 330; conflict; durable peace; gender; peace negotiations; women